Greenhouse Gas Emissions and Carbon Sinks of an Italian Natural Park - Grossi, Giampiero; Vitali, Andrea; Bernabucci, Umberto; Lacetera, Nicola; Nardone, Alessandro (Frontiers in Environmental Science, 2021)
Natural parks (NPs) have a primary role in supporting people’s welfare by maintaining natural and cultural resources. Various activities, such as those related to conservation of flora and fauna, forestry, agriculture and livestock, residential, and tourism, coexist within the boundaries of NPs. All these activities may contribute as a source or sink of carbon dioxide and, despite some NPs having started to promote their environmental services, there is currently a lack of information on their carbon footprint (CF). Although various international standards have provided guidelines to assess the CF of organizations, a lack of explicit formulation and procedure in these standards makes them difficult to apply, especially when the organizations to be evaluated embed a wide range of biological and anthropogenic activities. The framework proposed in this paper provides for the first time a holistic methodological approach to quantitatively and qualitatively estimate the annual greenhouse gas (GHG) emissions and removals occurring in NPs. The main data needed for the NP’s GHG inventory were directly collected on-site. The activity data and emissions factors as well as the methodologies involved were all referenced to their data sources, including the use of a biogeochemical model, IPCC equations, Ecoinvent database, and a literature review. This method highlighted that, by emitting 0.55 Mg CO2e ha−1 year−1, the NP generates an annual CF of about 3,300 Mg of CO2e. The agricultural activities with 43.4% of share showed the largest incidence, followed by wild fauna (17.8%), tourism (15.1%), and, to a lesser extent, all the other sectors considered in the assessment. On the other hand, when the annual soil and forest C sequestration rates were included in the balance, the NP contributes to sequester about 3.7 Mg CO2e ha−1 year−1, thus resulting in it being an important C-sink site (i.e., about 22,000 Mg CO2e year−1). By providing granular information on GHG emissions and carbon removals trend, the methodological approach involved in this study could help NPs in both planning effective mitigation strategies and supporting environmental certification processes. CF of NPs could increase tourists’ awareness of the important role that these protected natural areas have in climate change mitigation and adaptation.